1997
DOI: 10.1083/jcb.137.4.813
|View full text |Cite
|
Sign up to set email alerts
|

The Hsp70 Homologue Lhs1p Is Involved in a Novel Function of the Yeast Endoplasmic Reticulum, Refolding and Stabilization of Heat-denatured Protein Aggregates

Abstract: Heat stress is an obvious hazard, and mechanisms to recover from thermal damage, largely unknown as of yet, have evolved in all organisms. We have recently shown that a marker protein in the ER of Saccharomyces cerevisiae, denatured by exposure of cells to 50°C after preconditioning at 37°C, was reactivated by an ATP-dependent machinery, when the cells were returned to physiological temperature 24°C. Here we show that refolding of the marker enzyme Hsp150Δ–β-lactamase, inactivated and aggregated by the 50°C tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 54 publications
1
53
0
Order By: Relevance
“…This is consistent with the observation that the other ER NEF, SIL1 (suppressor of the ire1⌬ lhs1⌬ double mutant) (see below) can partially compensate for LHS1 in translocation when overexpressed (471). Lhs1 was found to be required for the refolding, solubilization, and reactivation of the marker protein Hsp150⌬-␤-lactamase after heat denaturation but interestingly played no role in its translocation, folding, and secretion under normal conditions (387). Two general conclusions can be drawn from these data.…”
Section: Er Nucleotide Exchange Factorssupporting
confidence: 73%
“…This is consistent with the observation that the other ER NEF, SIL1 (suppressor of the ire1⌬ lhs1⌬ double mutant) (see below) can partially compensate for LHS1 in translocation when overexpressed (471). Lhs1 was found to be required for the refolding, solubilization, and reactivation of the marker protein Hsp150⌬-␤-lactamase after heat denaturation but interestingly played no role in its translocation, folding, and secretion under normal conditions (387). Two general conclusions can be drawn from these data.…”
Section: Er Nucleotide Exchange Factorssupporting
confidence: 73%
“…They concluded from similar CPY pulse-chase refolding experiments with DTT that no translocation or folding defects are evident in cer1⌬ strains (Fig. 9C) (35). However, a translocation defect is clearly evident in their cer1⌬ strain pulse-chase 0-min time point.…”
Section: Discussionmentioning
confidence: 90%
“…The shorter times used in our study allowed the defect to be observed. However, the long times used points in the Saris et al (35) study did indicate that CPY does not accumulate and remain in the ER of a cer1 deletion strain for extended periods. Either the protein eventually folds in the ER and is transported to the Golgi in the absence of Cer1p or it is degraded in the ER.…”
Section: Discussionmentioning
confidence: 94%
“…Maintaining Kar2p in its active, cycling state may both keep luminal load down and keep Ire1p in its inactive form. To complicate this picture, Lhs1p has been shown to have chaperone activity itself, aside from its interaction with Kar2p (29).…”
Section: Discussionmentioning
confidence: 99%